Two Nominal Clause-Types in Northern Mansi: An Experimental Study of Language Variation - Csilla Horváth; Nikolett Mus (Linguistica Uralica, 2023)
The paper examines the structure and distribution of two types of Ânominal/adjectival predicates in the Northern Mansi language. A nominative noun or adjective serves as the predicate in one construction. The other predicate type contains a predicate noun or adjective that takes translative case marking. In both Âconstructions, the stative-like copula Ål- âbe, existâ can also appear, though under Âdifferent Âconditions. In the paper we focus on (a) the licensing conditions of the Ål- copula, (b) the Âpredicate-subject agreement morphology, and (c) concord within the predicate phrase in both predicates. Our findings demonstrate that the two types exhibit systematic structural differences: the copula Ål- is utilized in the nominative construction in the past, while it must be omitted in the present. The Ål- copula is always obligatory in the translative predicate. The nominative predicate noun/adjective takes the morpheme of the subject agreement in number, and we attested inter- and intra-speaker variation in Number concord in this construction when there is an overt copula in the predicate phrase. The translative-marked nominal/adjectival predicate does not take any inflectional suffix, and agreement that indicates both the person and the number of the subject is marked on the Ål- copula. ÂAdditionally, we will show that only the translative-type is acceptable in identificational clauses. As a result, the identificational reading/interpretation is where the Âsemantic Âdivision of labor between the two constructions lies. Our data come from fieldwork where Mansi native Âspeakers helped us with survey research. Northern Mansi newspaper texts were also used to clarify certain inconsistencies between our findings and the literature.